Prevalence of Escherichia coli and Salmonella spp from Chicken Meat Samples of Bharatpur, Chitwan - Thapa, R.; Thapa, D. B.; Chapagain, A. (Journal of the Institute of Agriculture and Animal Science, 2020)
Bacterial contamination and high antibiotic resistance properties of broiler chicken meat are of major risk to public consumers and poultry farming. With the major objective to determine the prevalence rate of E. coli and Salmonella and their antibiotic resistance properties we conducted this cross-sectional study for the period of three months (April- July, 2018) at National Avian Disease Investigation Laboratory, Bharatpur, Chitwan. A total of 100 samples were collected in sterile/dry plastic bags from different shops located in the vicinity of Bharatpur, and transported to the laboratory for further processing following standard microbiological techniques. Samples were crushed in mortar pestle followed by streaking on EMB agar and XLD agar for isolation of E. coli and Salmonella. Isolates were identified by determining their colony characters, gram staining and biochemical results. Major isolates in our study was E. coli (n=56/100; 56%) and isolation rate was higher from the fresh meat sample (n=51/70; 72.8%) and which was washed by ground water (n=63/88; 71.5%). Isolation rate of E. coli and Salmonella was not significantly associated with the areas from where the samples were collected in urban areas (for E. coli; p=0.68 and for Salmonella; p=0.50 respectively) however higher rate of isolation was seen form shop located in urban area. Antibiotic sensitivity testing revealed that Ciprofloxacin was most effective against E. coli (n=45/56; 80.3%) and Azithromycin was effective against Salmonella, (n=9/10; 90.0%) however, both isolates showed maximum resistance over Nalidixic Acid. This study is strongly indicative of improper sanitary practices for chicken meat handling and suggests for performing antibiotics susceptibility testing against the bacteria before prescribing any antibiotics.